2007
DOI: 10.1073/pnas.0610770104
|View full text |Cite
|
Sign up to set email alerts
|

Lung development and repair: Contribution of the ciliated lineage

Abstract: The identity of the endogenous epithelial cells in the adult lung that are responsible for normal turnover and repair after injury is still controversial. In part, this is due to a paucity of highly specific genetic lineage tools to follow efficiently the fate of the major epithelial cell populations: the basal, secretory, ciliated, neuroendocrine, and alveolar cells. As part of a program to address this problem we have used a 1-kb FOXJ1 promoter to drive CreER in the ciliated cells of the embryonic and adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
241
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(262 citation statements)
references
References 42 publications
21
241
0
Order By: Relevance
“…33 These findings are in accordance with a previous study, which utilized transgenic lineage tracing experiments in order to follow the fate of ciliated cells and provided strong evidence that ciliated cells do not proliferate or transdifferentiate into different epithelial cell types during repair of the naphthalene-injured mouse airway epithelium. 10 In addition, we found that many of the proliferating (ie, Ki-67-positive) cells detected within the regenerating airway epithelium were also dually positive for CC10/CCSP in both Elf3 þ / þ and Elf3À/À mice. We speculate that these cells may represent a naphthalene-resistant sub-population of CC10/CCSPexpressing progenitor cells, which are also known as vCE cells.…”
Section: Discussionmentioning
confidence: 77%
“…33 These findings are in accordance with a previous study, which utilized transgenic lineage tracing experiments in order to follow the fate of ciliated cells and provided strong evidence that ciliated cells do not proliferate or transdifferentiate into different epithelial cell types during repair of the naphthalene-injured mouse airway epithelium. 10 In addition, we found that many of the proliferating (ie, Ki-67-positive) cells detected within the regenerating airway epithelium were also dually positive for CC10/CCSP in both Elf3 þ / þ and Elf3À/À mice. We speculate that these cells may represent a naphthalene-resistant sub-population of CC10/CCSPexpressing progenitor cells, which are also known as vCE cells.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, a fragment of the FOXJ1 promoter that has previously been shown to drive expression specifically in ciliated cells 15,28,29 was used to target the expression of CFTR in a murine model of CF. RNA analysis demonstrated that the FOXJ1 promoter successfully targeted the expression of CFTR to the ciliated epithelium of the airways, and the level of mRNA was greater than or equal to the level of endogenous mouse CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of the airway epithelium has been observed to move down the airways from the proximal to the more distal regions (McDowell et al, 1994;Toskala et al, 2005). Molecular markers for NE cell fate specification (for example, the transcription factor Ascl1) and Clara and ciliated cell differentiation (Secretoglobin1a1 and the transcription factor Foxj1) are first observed at E12.5 (NE cells) and E14.5, or 15.5 (ciliated and Clara cells), always at least one airway generation from the multipotent progenitors in the distal tip (Rawlins et al, 2007;McGovern et al, 2010).…”
Section: Lineage-restricted Epithelial Progenitorsmentioning
confidence: 99%